Effect of Surya Namaskar yoga practice on flexibility in the pre-elderly and elderly - Karasugi, Ni Made Ayu Regina; Lilis, Lilis; Amita, Angela Shinta Dewi; Novi Handayani, Maria Dara; Prastowo, Nawanto Agung (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Anatomical and physiological changes occur along with the aging process. One of the changes is decreased flexibility due to changes in the musculoskeletal system. Upper and lower limb flexibility is closely related to the ability to carry out daily activities, which affects the quality of life of the elderly. Surya  Namaskar yoga is known to help increase flexibility because it integrates stretching components within its movement. This study aimed to investigate the effect of Surya  Namaskar on flexibility in the pre-elderly and elderly. It was is quasi-experimental study with a pre-experimental one-group pretest-posttest research design. A total of 20 participants were selected using consecutive sampling according to the inclusion criteria. Flexibility measurements of the upper and lower limbs were carried out before and after the intervention using the back scratch test and chair sit and reach test methods. Surya  Namaskar intervention was carried out for 8 wk. Data were analyzed using the Shapiro-Wilk normality test, paired t-test, and Wilcoxon test. The results showed that there was a highly significant difference between the mean value of the back-scratch test (for upper limb flexibility) before and after the intervention (p<0.001). Significant differences were also found in the mean values of chair-sit-and-reach test measurements (for lower extremity flexibility) before and after the intervention (p<0.001). In conclusion, Surya  Namaskar exercises can improve the flexibility of the upper and lower extremities in the pre-elderly and elderly.